Procedure for admitting and acting extemporaneous evidence in the Peruvian labor process - Chávez Paucar, Juan Carlos (2020)
This article addresses the issue of the extemporaneous offering of evidentiary means in the labor process, formulated at or after the trial hearing, or after the first instance judgment has been issued. It develops the principles and foundations, the assumptions, requirements and presupposition of the admission in this process. A uniform procedure for the admission and legal action of extemporaneous evidence is proposed in this article. It is eminently practical and based on the experience acquired in the daily judicial work as a magistrate.